2023
DOI: 10.1038/s41598-023-43118-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural climate solutions provide robust carbon mitigation capacity under future climate change scenarios

David C. Marvin,
Benjamin M. Sleeter,
D. Richard Cameron
et al.

Abstract: Natural climate solutions (NCS) are recognized as an important tool for governments to reduce greenhouse gas emissions and remove atmospheric carbon dioxide. Using California as a globally relevant reference, we evaluate the magnitude of biological climate mitigation potential from NCS starting in 2020 under four climate change scenarios. By mid-century NCS implementation leads to a large increase in net carbon stored, flipping the state from a net source to a net sink in two scenarios. Forest and conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Some studies focus on the current research status [8][9][10][11][12][13], whereas others focus on research methods from carbon emissions [14][15][16][17][18][19][20][21] or carbon sink [22][23][24][25][26][27]. Moreover, some research noticed the determinants and future carbon emission reduction measures [28][29][30][31]. For example, scholars have explored the relationship between highquality urbanization and energy transition in connecting land use, carbon emissions, and carbon sink [9,17].…”
Section: Used Terrestrial Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focus on the current research status [8][9][10][11][12][13], whereas others focus on research methods from carbon emissions [14][15][16][17][18][19][20][21] or carbon sink [22][23][24][25][26][27]. Moreover, some research noticed the determinants and future carbon emission reduction measures [28][29][30][31]. For example, scholars have explored the relationship between highquality urbanization and energy transition in connecting land use, carbon emissions, and carbon sink [9,17].…”
Section: Used Terrestrial Ecosystemmentioning
confidence: 99%
“…Recent research has analyzed the influencing factors, differences, comparisons and mitigation policies regarding LUCES to understand its relationship to nature, resources, environment, society and technology [33,36]. Marvin et al, (2023) found that the implementation of nature-based climate solutions, such as forests, would contribute 85% of the carbon emission reductions [29]. Climate change had two types of impacts on land use change and carbon emissions.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Reforestation is an essential component of natural climate solutions to help achieve climate goals based on multiple analyses worldwide (Griscom et al, 2017;Bastin et al, 2019;Marvin et al, 2023). This Frontiers contribution makes the argument that to unlock this potential, we must advance the science of "right tree, right place" to a new level of customization for climate resilience, mitigation, and co-benefits such as biodiversity while also strategically using reforestation to enhance fiber supplies to support diverse forest products that offer climate change mitigation benefits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, not all landscapes may be appropriate for NCS projects. Some have competing socioeconomic uses (e.g., forestry, agriculture, and/or indigenous land) (Hasegawa et al, 2018), some are projected to become too dry to sustain growing plant biomass (Marvin et al, 2023), and others are already rich in soil organic carbon (SOC) (Bossio et al, 2020). The variation in land use and resource availability constraints both the technical and realizable potential for C drawdown and permanence because no single NCS method is appropriate for all bioclimatic conditions (Baldocchi et al, 2018).…”
mentioning
confidence: 99%
“…Here, we present a geographic-based framework for guiding NCS implementation using soil C stocks (a proxy for belowground sequestration) and projected climate change (a control on future drawdown potential) across multiple ecoregions in the Pacific Northwest (PNW) of the United States. In accordance with a "protect-manage-restore" approach to NCS implementation (Cook-Patton et al, 2021) that also considers future changes in climate (Marvin et al, 2023), the ecoregions considered here provide examples of how sector-specific NCS activities (e.g., forestry and agriculture) can be ranked relative to conservation and thus prioritized to inform decisions.…”
mentioning
confidence: 99%